THE INFLUENCE OF VIDEO AND READING INTEREST IN IMPROVING READING COMPREHENSION ACHIEVEMENT TO THE NINTH GRADERS OF XAVERIUS JUNIOR HIGH SCHOOL 1 OF PALEMBANG - Hendri Hendri (ELTE Journal (English Languange Teaching and Education), 2014)
ABSTRACTThe writer was interested in conducting this research in accordance that the students' reading comprehension achievement was still low. One of media interaction that is used in this study is video. It is expected that through video, the students can be interested and motivated in learning English, especially reading. In this case, the writer intends to the use of video in improving the students’ reading comprehension achievement. The writer hopes that it will give the visualization about the contents of text, so the students can understand it easier. This research was conducted in experimental research using factorial design to 96 students of the ninth graders of Xaverius Junior High School 1 of Palembang in the first semester of the academic year of 2013-2014. The objectives of this research were to find out whether or not (1) There was a significant difference in average of reading comprehension achievement between the students who were taught using video and those who are taught using conventional strategy (2) There was a significant difference in average of reading comprehension achievement between the students who were in high, middle, and low interest after being taught using video and those after being taught using conventional strategy and (3) There was a significant interaction effect of using video and reading interest on the students’ reading comprehension achievement. There were some instruments to achieve the purpose of this research. There was a significant difference of high, middle and low reading interest on the students’ reading comprehension achievement. It meant that video and reading interest gave a significant influence for the students’ reading comprehension achievement because there was a significant improvement in average of the students’ reading comprehension achievement. Key words: Video, Reading Interest, and Reading Comprehension Achievement